Diversidade de mamíferos de médio porte e ocorrência de cães domésticos como espécie invasora em unidades de conservação na Mata Atlântica da Paraíba, Brasil. - Albuquerque, Anna Carolina Figueiredo de (2017)
In Northeastern of Brazil, the Atlantic Forest portion north to the São Francisco River, known as the Pernambuco Endemism Center (PEC), a biodiversity hotspot, is the most impacted and fragmented region of the biome. Little is known about the medium-sized mammalian fauna in this region, despite their ecological role as key species in the structuring of biological communities, especially in the absence of large predators. With the processes of anthropization and the expansion of urbanized areas close to natural environments, there is an increase in the population of domestic mammals, which end up directly affecting wild mammals through competition, predation and/or transmission of parasites. This study aimed to analyze the structure of medium - sized mammal communities through the species composition, richness and diversity, in three Atlantic Forest conservation units in the state of Paraíba. Also, we evaluated the presence of domestic dogs as invasive species, estimating their abundance, density, pattern of use of the space and activity. The study was carried out in the Guaribas Biological Reserve (Rebio) and two Natural Heritage Private Reserves (RPPN), Fazenda Pacatuba and Engenho Gargaú. For that, we used cameras traps distributed in grids with interval of 1km². We obtained 642 records of wild mammals, belonging to 14 species and 86 domestic dogs and cats’ records. The most representative order was the Carnivora, and the most frequent species were Dasyprocta iacki (n = 255; 35%), Didelphis. albiventris (n = 184; 25%) and Dasypus novemcinctus (n = 60; 8%). We highlight the records of Leopardus pardalis, which are the first for the species in the study area We should also note the registration of Cabassous tatouay, which has only two specimens in the Mammalian Collection of the Federal University of Paraíba, Coendou prehensilis, for being arboreal species, besides the primates, Alouatta belzebul and Sapajus flavius, which are critically endangered. The wild mammals’ richness we found represented half of the regional pool of species, which may be related to high fragmentation and habitat loss in the area but may be also related to practices of hunting that occur in the region, resulting in a defaunation process. The high frequency of Didelphis albiventris, can be an indicative of disturbed areas, as well as the absence of carnivorous species expected for region can generate a cascade effect in the biological communities. In relation to the domestic dogs, we estimated the abundance and density in Rebio Guaribas SEMA II (n = 90, 3.2 dogs / km²) and RPPN Fazenda. Pacatuba (n = 29, 6.2 dogs / km²), respectively. The activity hours of the dogs in the protected areas had peaks between 1: 00-3: 00 AM and 5: 00-07: 00 AM, and the pattern of use was more frequent at the edges in the RPPN Faz. Pacatuba, and in Rebio Guaribas, on the edge as well on its internal roads. The records found of dogs in the conservation units are relevant strategic planning to avoid the use of these areas by these dogs since they are considered invasive species and can have negative impacts to the fauna. Actions involving the surrounding communities of the areas to explain the health problems between the interaction of wild dogs and mammals. And can cause as well as the accomplishment of canine population censuses concomitant with epidemiological studies and campaigns of vaccination and castration in the dogs of the communities of the areas must also be carried out.